2015
DOI: 10.1177/1470320314565840
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analyses of CYP17A1 genetic polymorphisms and coronary artery disease in a Uygur population

Abstract: Background: The relationship between CYP17A1 genetic polymorphisms and coronary artery disease (CAD) remains unclear. The aim of the present study was to assess the association between CYP17A1 gene polymorphism and CAD in a Chinese Uygur population. Methods: A total of 493 people including 266 patients and 227 controls were selected for the present study. All CAD patients and controls were genotyped for the same five single nucleotide polymorphisms (SNPs) (rs4919686, rs1004467, rs4919687, rs10786712, and rs248… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
2
3
0
2
Order By: Relevance
“…Thus physiological testosterone replacement could be an option to rescue the phenotype in mice 50 without any need of genetic modification of Cyp17a1 expression. Further these data support the GWAS finding that the chromosomal region containing the CYP17A1 gene is associated with CAD and pinpoint CYP17A1 as the causal gene at this locus 2,39,40 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Thus physiological testosterone replacement could be an option to rescue the phenotype in mice 50 without any need of genetic modification of Cyp17a1 expression. Further these data support the GWAS finding that the chromosomal region containing the CYP17A1 gene is associated with CAD and pinpoint CYP17A1 as the causal gene at this locus 2,39,40 .…”
Section: Discussionsupporting
confidence: 83%
“…Such disorders are also associated with various cardiovascular risk factors, including hypertension [32][33][34][35][36][37] , diabetes, and aortic stiffness 38 . Here we focused on CYP17A1, a gene mapping to a locus associated with various cardiovascular disorders, including CAD, MI, diabetes, and arterial stiffness, according to GWAS 3,33,34,[38][39][40] .…”
Section: Discussionmentioning
confidence: 99%
“…However, environmental factors are not the best predictors of CAD risk, suggesting that genetic variants might influence the development of CAD. Previous studies have reported that a number of genetic polymorphisms might play an important role in the development of CAD including cytochrome P450 17A1 (CYP17A1), toll-like receptors, metallothionein 2A, and retinol binding protein 4, as well as matrix metalloproteinase 1 (Qintao et al, 2014;Wan et al, 2014;Yang et al, 2014;Dai et al, 2015;Guven et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rs1004467, which is in the intron region of CYP17A1, has been associated with cardiovascular diseases. Specifically, two case–control studies have reported rs1004467 to be significantly associated with CAD in Chinese populations ( 14 , 26 ). Furthermore, another case–control study found that rs1004467 in CYP17A1 was associated with arterial stiffness in 326 prediabetic and 743 diabetic subjects ( 27 ).…”
Section: Discussionmentioning
confidence: 99%